The measurement of vitrinite reflectance with MatLab - Fernandes, Paulo (2014)
The measurement of vitrinite reflectance is widely used as an indicator of coal rank and organic maturation in source-rock studies. This is due to the regular change in reflectance properties of the vitrinite group during coalification.